Controlling the Mobility of Ionic Liquids in the Nanopores of MOFs by Adjusting the Pore Size: From Conduction Collapse by Mutual Pore Blocking to Unhindered Ion Transport. Issue 39 (24th August 2022) - Zhang, Zejun; Liu, Modan; Li, Chun; Wenzel, Wolfgang; Heinke, Lars
Abstract: Ionic liquids (ILs) in nanoporous confinement are the core of many supercapacitors and batteries, where the mobility of the nanoconfined ILs is crucial. Here, by combining experiments based on impedance spectroscopy with molecular dynamics simulations, the mobility of a prototype IL in the nanopores of an isoreticular metal‐organic framework (MOF)‐series with different pore sizes is explored, where an external electric field is applied. It has been found that the conduction behavior changes tremendously depend on the pore size. For small‐pore apertures, the IL cations and anions cannot pass the pore window simultaneously, causing the ions to mutually block the pores. This results in a strong concentration dependence of the ionic conduction, where the conduction drops by two orders of magnitude when filling the pores. For large‐pore MOFs, the mutual hindrance of the ions in the pores is small, causing only a small concentration dependence. The cutoff between the large‐pore and small‐pore behavior is approximately the size of a cation‐anion‐dimer and increasing the pore diameter by only 0.2 nm changes the conduction behavior fundamentally. This study shows that the pore aperture size has a substantial effect on the mobility of ions in nanoporous confinement and has to be carefully optimized for realizing highly‐mobile nanoconfined ILs. Abstract : The electric‐field‐driven motion of ionic liquids in the nanopores of a series of metal‐organic frameworks (MOFs) is governed by the pore aperture, showing a sharp cutoff. While the ions are mobile in large‐pore MOFs, a conduction collapse is caused in small‐pore MOFs where the cations and anions mutually block the pore apertures.